2003
DOI: 10.1053/jhep.2003.50310
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Immune Response During Hbv and Hcv Infection

Abstract: The innate immune system has a role not only in protecting the host during the initial period of virus infection, but also in shaping the nature of the adaptive immune response. In this review, we follow the kinetics of the virologic and immunologic events occurring from the time of hepatitis B virus (HBV) and hepatitis C virus (HCV) infection. We primarily discuss how the early events after infection might influence the development of the adaptive immune response in these 2 important viral infections and how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
174
0
13

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(192 citation statements)
references
References 141 publications
(227 reference statements)
5
174
0
13
Order By: Relevance
“…Studies of acute HBV infection in primates and humans reveal an initial quiescent phase of Ϸ4-7 weeks before HBV starts to replicate vigorously, reaching levels of 10 9 to 10 10 copies per milliliter (26)(27)(28). Activation of components of the innate immune system are likely to play a central role in control of this initial HBV burst because HBV-DNA quantity decreases by almost 90% well in advance of the appearance of an antigen-specific CD8 ϩ T cell response and hepatopathology (27)(28)(29)(30)(31). However, identification of the individual components of the innate immune system responsible for this rapid down-regulation of viral replication, and the mechanism of activation, has been elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of acute HBV infection in primates and humans reveal an initial quiescent phase of Ϸ4-7 weeks before HBV starts to replicate vigorously, reaching levels of 10 9 to 10 10 copies per milliliter (26)(27)(28). Activation of components of the innate immune system are likely to play a central role in control of this initial HBV burst because HBV-DNA quantity decreases by almost 90% well in advance of the appearance of an antigen-specific CD8 ϩ T cell response and hepatopathology (27)(28)(29)(30)(31). However, identification of the individual components of the innate immune system responsible for this rapid down-regulation of viral replication, and the mechanism of activation, has been elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Today, there is an increasing evidence that the immune response against hepatitis C virus (HCV), in particular, the cell-mediated response and the host genetic factors contribute to the natural history of HCV infection [1][2][3][4][5][6]. Clinical research showed the prominent role of T helper cell type 1 (Th1) or pro-inflammatory and type 2 (Th2) or anti-inflammatory cytokines in the pathogenesis of chronic hepatitis C. Indeed, a positive correlation between Th1 cytokine levels or Th1-type cell percentage and histological fibrosis or progressive liver injury in chronic hepatitis C was detected [7].…”
Section: Introductionmentioning
confidence: 99%
“…Many hypotheses have been proposed, including the inability of the host to carry out an efficient humoral and cellular response, allowing immune escape of these highly changeable viruses (quasispecies) [Guglietta et al, 2005]; the high rate of HCV replication, which would lead to the exhaustion of CD4 þ T-cells through the production of large amounts of HCV antigens [Kantzanou et al, 2003]; the suppression of HCV-specific CD4 þ T-cell expansion [Klugewitz et al, 2002]; the intrahepatic compartmentalization and induction of apoptosis of virus-specific CD8 þ T-cells [Crispe et al, 2000]; the production of immunomodulatory proteins by HCV [Large et al, 1999]; and the inability of the innate immune response to promote appropriate T-cell stimulation [Bertoletti and Ferrari, 2003].…”
Section: Introductionmentioning
confidence: 99%